1994
DOI: 10.1002/art.1780370517
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of crosslinks pyridinoline and pentosidine in articular cartilage of patients with bone and joint disorders

Abstract: Objective. To determine the content of two crosslinks, pyridinoline (a mature crosslink) and pentosidine (a senescent crosslink), in human articular cartilage, and to examine the effect of bone and joint disorders on the content 9f those crosslinks in articular cartilage.Methods. After pretreatment with SP-Sephadex C-25, high-performance liquid chromatography was conducted on a hydrolysate of human articular cartilage from 53 patients with one of the following diseases: osteoarthritis (OA), rheumatoid arthriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
1
1

Year Published

1996
1996
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 17 publications
(6 reference statements)
4
57
1
1
Order By: Relevance
“…Histopathological studies have shown AGE accumulation in a variety of tissue types, including coronary atheroma, renal cortex, mesangium and glomerular basement membrane [12], as well as the dermal layer [13], amyloid plaques in Alzheimer's disease [14], cartilage in rheumatoid arthritis [15], cardiac muscle, lung and liver [16].…”
Section: Introductionmentioning
confidence: 99%
“…Histopathological studies have shown AGE accumulation in a variety of tissue types, including coronary atheroma, renal cortex, mesangium and glomerular basement membrane [12], as well as the dermal layer [13], amyloid plaques in Alzheimer's disease [14], cartilage in rheumatoid arthritis [15], cardiac muscle, lung and liver [16].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that pentosidine accumulated with age in tissues such as dura mater (1), lens (6), skin (17), cartilage (14,18), glomerular basement membrane (19), aorta (20), and meniscus (21). However, there have been few reports on the measurements of pentosidine in body fluids and on the age relationship of pentosidine therein.…”
Section: Discussionmentioning
confidence: 96%
“…Chromatographic methods are usually based on the determination of the crosslinks in urine, because higher concentrations of the metabolites are found in urine compared with other body fluids. The determination of pyridinium crosslinks has been described in serum and plasma (7,21), in cartilage (22), and in synovial fluid (23).…”
Section: Discussionmentioning
confidence: 99%